Disability in multiple sclerosis is related to thalamic connectivity and cortical network atrophy. (January 2022) - Schoonheim, Menno M; Pinter, Daniela; Prouskas, Stefanos E; Broeders, Tommy AA; Pirpamer, Lukas; Khalil, Michael; Ropele, Stefan; Uitdehaag, Bernard MJ; Barkhof, Frederik; Enzinger, Christian; Geurts, Jeroen JG
Background: Thalamic atrophy is proposed to be a major predictor of disability progression in multiple sclerosis (MS), while thalamic function remains understudied. Objectives: To study how thalamic functional connectivity (FC) is related to disability and thalamic or cortical network atrophy in two large MS cohorts. Methods: Structural and resting-state functional magnetic resonance imaging (fMRI) was obtained in 673 subjects from Amsterdam (MS: N  = 332, healthy controls (HC): N  = 96) and Graz (MS: N  = 180, HC: N  = 65) with comparable protocols, including disability measurements in MS (Expanded Disability Status Scale, EDSS). Atrophy was measured for the thalamus and seven well-recognized resting-state networks. Static and dynamic thalamic FC with these networks was correlated with disability. Significant correlates were included in a backward multivariate regression model. Results: Disability was most strongly related (adjusted R 2  = 0.57, p  < 0.001) to higher age, a progressive phenotype, thalamic atrophy and increased static thalamic FC with the sensorimotor network (SMN). Static thalamus–SMN FC was significantly higher in patients with high disability (EDSS ⩾ 4) and related to network atrophy but not thalamic atrophy or lesion volumes. Conclusion: The severity of disability in MS was related to increased static thalamic FC with the SMN. Thalamic FC changes were only related to cortical network atrophy, but not to thalamic atrophy.